Convergent validity between willingness to pay elicitation methods: an application to Grand Canyon whitewater boaters. Issue 4 (21st March 2019) - Neher, Christopher; Bair, Lucas; Duffield, John; Patterson, David; Neher, Katherine
Abstract : We directly compare trip willingness to pay (WTP) values between dichotomous choice contingent valuation (DCCV) and discrete choice experiment (DCE) stated preference surveys of private party Grand Canyon whitewater boaters. The consistency of DCCV and DCE estimates is debated in the literature, and this study contributes to the body of work comparing the methods. Comparisons were made of mean WTP estimates for four hypothetical Colorado River flow-level scenarios. Boaters were found to most highly value mid-range flows, with very low and very high flows eliciting lower WTP estimates across both DCE and DCCV surveys. Mean WTP precision was estimated through simulation. No statistically significant differences were detected between the two methods at three of the four hypothetical flow levels.